Studying the relationship between advanced oxidative stress of protein and uterine disturbance in dairy cows - Hassan, Saeed Kazem; Al-Najar, Eftkar Mahdy (Journal of Kerbala for Agricultural Sciences, 2023)
The study was conducted on 100 dairy cows in Tag-Alnahrain station, located in Al-Qadysia province, post parturition (after 40-60) days after calving. The aim of the study was to test the relationship between oxidative stress, particularly protein oxidation, and uterine health during the puerperium. The cows are divided into four groups according to intense clinical sighs of merit. In order to distinguish between degrees of inflammation, in this study, the cutoff value of PMN %. was set at 8% to distinguish between degrees of inflammation. The group (H) was (54). The SCE group consisted of 22 cows infected with subclinical endometritis, the EM1 group consisted of 11 cows infected with clinical endometritis Grade 1, and the EM2 group consisted of 13 cows infected with clinical endometriosis Grade 2. The advanced oxidation protein product (AOPP) was estimated in plasma and vaginal mucus discharges by using a commercial laboratory method to detect the dityrosin formation, which is the major content of AOPP. AOPP, a good marker of protein oxidation, was visualised by western blot,. The study demonstrated that there was an increase in plasma AOPP in the EM2 group with a significant value of p 0.01.The study also showed a significantly increased concentration of AOPP in vaginal mucus discharges in the group of animals infected with (SCE). The study clarified that there was an increase in neutrophil point age of more than 8% in vaginal mucus discharge after collecting mucus by metrecheek in the (EM1) group with a significant value of p≤0.0l while it was significantly(p≤0.01) in uterine mucus collected by cytobrush.